2022
DOI: 10.54029/2022cnz
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function index in embolic stroke of undetermined source: A case-control study

Abstract: Background & Objectives: Previous studies showed left atrial volume index (LAVi) is a precise surrogate of atrial cardiopathy and associated with new-onset atrial fibrillation and embolic stroke undetermined source (ESUS). Recent data suggest that the left atrial functional index (LAFi) is associated with the risk of developing AF recurrence. However, there was no study to show LAFi in ESUS. We aim to compare the performance of different surrogates of atrial cardiopathy (LAVi and LAFi) in a cohort of ESUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
1
1
Order By: Relevance
“…Nonetheless, recent studies, such as Saadatnia et al showed a correlation between atrial pathology markers and ischemic stroke, and suggested that the tissue substrate, rather than the arrhythmic state, could be the most important trigger of stroke risk. 9 Our results are not in line with Hart et al They compared a daily dose of 15 mg of rivaroxaban to 100 mg of aspirin for stroke prevention after embolic stroke of undetermined source (ESUS). They concluded rivaroxaban was not superior to aspirin with regard to the prevention of recurrent stroke after an initial embolic stroke of undetermined source and was associated with a higher risk of bleeding.…”
Section: Discussioncontrasting
confidence: 93%
“…Nonetheless, recent studies, such as Saadatnia et al showed a correlation between atrial pathology markers and ischemic stroke, and suggested that the tissue substrate, rather than the arrhythmic state, could be the most important trigger of stroke risk. 9 Our results are not in line with Hart et al They compared a daily dose of 15 mg of rivaroxaban to 100 mg of aspirin for stroke prevention after embolic stroke of undetermined source (ESUS). They concluded rivaroxaban was not superior to aspirin with regard to the prevention of recurrent stroke after an initial embolic stroke of undetermined source and was associated with a higher risk of bleeding.…”
Section: Discussioncontrasting
confidence: 93%
“…We initially identified 6897 articles, with 4292 excluded as duplicates and 2402 excluded as nonrelevant based on title and abstract screening. Full text was examined in 200 articles, with 29 fulfilling inclusion criteria for data analysis 6,7,14–40 …”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined meta‐regression bubble plots and performed an exclusion analysis to identify outlier studies for sources of influence. A number of studies were identified over all meta‐analysis studies, with resolution of heterogeneity observed following their exclusion 6,16,21–23,26,28,30,32,34,35,37,39 . Notably, the majority of outlier studies were observed in studies comparing CS‐ESUS to HC, indicating probable unidentified clinical covariates in patients compared with healthy participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations